Nonaqueous redox-flow batteries: features, challenges, and prospects. (May 2015) - Huang, Yan; Gu, Shuang; Yan, Yushan; Li, Sam Fong Yau
Highlights: Redox flow batteries (RFBs) are promising energy storage technologies. Non-aqueous RFBs have wider voltage windows than aqueous RFBs. Non-aqueous RFBs have faster electron transfer kinetics than aqueous RFBs. Non-aqueous RFBs also have wider working temperature range than aqueous RFBs. Abstract : The increasing concern over climate changes and the limited supply of fossil fuels bring into the general realization that we urgently need to maximize the use of renewable energy resources such as solar and wind. Redox-flow batteries are one of the most promising energy storage technologies, overcoming the intermittency of solar and wind energy. In this review, we focus on nonaqueous redox-flow batteries because of their appealing features in comparison with aqueous based systems, including wider voltage windows, intrinsically faster electron-transfer kinetics, and more extended working temperature ranges. The limitations and challenges of nonaqueous redox-flow batteries are also discussed to provide information for the further development of nonaqueous redox-flow batteries.